Burkina Faso - Ninigui Village - Yatenga - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Adapting to climate change in Burkina Faso. Farmers need to change the way they farm and how they hold livestock. The farmers shown in this batch have all included creative ways in order to adapt to the changes in the unpredictable weather.